Advancements and limitations of LLMs in replicating human color-word associations - Makoto Fukushima; Shusuke Eshita; Hiroshige Fukuhara (Discover Artificial Intelligence)
Abstract Color-word associations play a fundamental role in human cognition and design applications. Large Language Models (LLMs) have become widely available and have demonstrated intelligent behaviors in various benchmarks with natural conversation skills. However, their ability to replicate human color-word associations remains understudied. We compared multiple generations of LLMs (from GPT-3 to GPT-4o) against human color-word associations using data collected from over 10,000 Japanese participants, involving 17 colors and 80 words (10 word from eight categories) in Japanese. Our findings reveal a clear progression in LLM performance across generations, with GPT-4o achieving the highest accuracy in predicting the best voted word for each color and category. However, the highest median performance was approximately 50% even for GPT-4o with visual inputs (chance level of 10%). Moreover, we found performance variations across word categories and colors: while LLMs tended to excel in categories such as Rhythm and Landscape, they struggled with categories such as Emotion. Interestingly, color discrimination ability-estimated from our color-word association data showed high correlation with human color discrimination patterns, consistent with previous studies. Thus, despite reasonable alignment in basic color discrimination, humans and LLMs still diverge systematically in the words they assign to those colors. Our study highlights both the advancements in LLM capabilities and their persistent limitations, raising the possibility of systematic differences in semantic memory structures between humans and LLMs in representing color-word associations.